HUBUNGAN GAYA BELAJAR DENGAN HASIL BELAJAR SENI RUPA DI SMP NEGERI 1 LUBUK BASUNG - RAISA AULIA, Drs. Eswendi, M.Pd., Drs. Wisdiarman, M.Pd. (Serupa The Journal of Art Education, 2016)
This research aims at describing the correlation between the learning style and result of fine arts learning at SMPN 1 Lubuk Basung. It is quantitative research, and the sample is 86 students from VII,VIII,and IX grades. The sampling technique uses Stratified Random Sampling. The technique of collecting data uses questionnaire. Analysis test requirement uses normality test and product moment correlation. The result of the study showed that (1) The average of students ‘learning style at SMPN 1 Lubuk Basung was 3.71 with good categories, (2) the average of mid-term test was 3.23 with good category, and (3) there was positive and significant correlation between learning style and result of fine arts learning. Person correlation is 0.000 < 0.05 which means Ha is accepted.Kata kunci: gaya belajar, hasil belajar